Perturbed cholesterol and vesicular trafficking associated with dengue blocking in Wolbachia-infected Aedes aegypti cells - Vincent Geoghegan; Kirsty Stainton; Stephanie M. Rainey; Thomas H. Ant; Adam A. Dowle; Tony Larson; Svenja Hester; Philip D. Charles; Benjamin Thomas; Steven P. Sinkins (Nature Communications, 2017)
Wolbachia infection of mosquitoes can block dengue virus infection and is tested in field trials, but the mechanism of action is unclear. Using proteomics, Geoghegan et al. here identify effects of Wolbachia on cholesterol homeostasis and dengue virus replication in Aedes aegypti.